PERLINDUNGAN HUKUM KEPEMILIKAN DAN HAK CIPTA ATAS KONTEN DIGITAL DI ERA EKONOMI KREATIF - Sapta Nur Fallah (CV. Adiba Aisha Amira, 2025)
Legal protection of ownership and copyright of digital content has become a crucial issue in the creative economy era, which is characterised by rapid developments in information technology. This study aims to analyse the forms of legal protection applicable in Indonesia to digital content copyright, the challenges faced in its implementation, and possible solutions. The study was conducted using a normative legal method through literature review, legislation, and other relevant documents. The results of the study indicate that although Law No. 28 of 2014 on Copyright provides a fairly comprehensive legal protection framework, practices in the field still face obstacles such as low legal awareness, ease of infringement in the digital realm, and limitations in law enforcement. Strengthening regulations, leveraging digital protection technologies, and fostering cross-sector collaboration are necessary to create a fair and sustainable creative economy ecosystem.